2017
DOI: 10.1002/aenm.201702337
|View full text |Cite
|
Sign up to set email alerts
|

Elastic Sandwich‐Type rGO–VS2/S Composites with High Tap Density: Structural and Chemical Cooperativity Enabling Lithium–Sulfur Batteries with High Energy Density

Abstract: Driven by increasing demand for high‐energy‐density batteries for consumer electronics and electric vehicles, substantial progress is achieved in the development of long‐life lithium–sulfur (Li–S) batteries. Less attention is given to Li–S batteries with high volume energy density, which is crucial for applications in compact space. Here, a series of elastic sandwich‐structured cathode materials consisting of alternating VS2‐attached reduced graphene oxide (rGO) sheets and active sulfur layers are reported. Du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
202
1

Year Published

2018
2018
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 255 publications
(205 citation statements)
references
References 62 publications
2
202
1
Order By: Relevance
“…As shown in Figure 6c, G-VS 2 with different sulfur loadings has been examined by cycling at 1 C. After 150 cycles, a reversible capacity of 923, 559, and 520 mAh g −1 is retained with sulfur loadings of 1.0, 2.0, and 3.5 mg cm −2 , corresponding to capacity retentions of 72.7%, 71.1%, and 74.2%, respectively. Impressively, a systematic study with respect to rGO-VS 2 as sulfur hosts has recently been demonstrated realizing high energy density and tap density, [32] it is noted that our work is otherwise differentiated by certain key aspects from synthetic procedure of products through theoretical considerations, to electrochemical performances at high rates and high sulfur loadings. Moreover, deep cycling of sulfur-loaded electrodes (1.3 and 2.0 mg cm −2 ) at 2 C rate also discloses capacity stabilities over 200 cycles ( Figure S16, Supporting Information).…”
Section: Doi: 101002/aenm201800201mentioning
confidence: 99%
See 2 more Smart Citations
“…As shown in Figure 6c, G-VS 2 with different sulfur loadings has been examined by cycling at 1 C. After 150 cycles, a reversible capacity of 923, 559, and 520 mAh g −1 is retained with sulfur loadings of 1.0, 2.0, and 3.5 mg cm −2 , corresponding to capacity retentions of 72.7%, 71.1%, and 74.2%, respectively. Impressively, a systematic study with respect to rGO-VS 2 as sulfur hosts has recently been demonstrated realizing high energy density and tap density, [32] it is noted that our work is otherwise differentiated by certain key aspects from synthetic procedure of products through theoretical considerations, to electrochemical performances at high rates and high sulfur loadings. Moreover, deep cycling of sulfur-loaded electrodes (1.3 and 2.0 mg cm −2 ) at 2 C rate also discloses capacity stabilities over 200 cycles ( Figure S16, Supporting Information).…”
Section: Doi: 101002/aenm201800201mentioning
confidence: 99%
“…The metallic feature has already enabled VS 2 , especially its 2D form, to become a versatile platform for multifunctional applications such as supercapacitor, [26] nanoelectronics, [27][28][29] and hydrogen evolution. [19,32,33] It is worth noting that most of the fabrication strategies involved in these pioneer work for VS 2 -based sulfur cathodes normally dealt with simple mechanical/physical mixing of VS 2 nanostructures with carbonaceous materials, which could result in an uneven distribution of VS 2 and an ineffective contact in between. [19,32,33] It is worth noting that most of the fabrication strategies involved in these pioneer work for VS 2 -based sulfur cathodes normally dealt with simple mechanical/physical mixing of VS 2 nanostructures with carbonaceous materials, which could result in an uneven distribution of VS 2 and an ineffective contact in between.…”
Section: Doi: 101002/aenm201800201mentioning
confidence: 99%
See 1 more Smart Citation
“…[29] ii) They should have suitable Li diffusion characteristics with highly efficient polysulfide attraction and adsorption. [35][36][37][38][39] Disappointingly, however, only very few 2D materials, including phosphorene [40] and defective borophene, [41] have so far been able to simultaneously satisfy the abovementioned two criteria while these coupling materials have yet to be fully explored. [35][36][37][38][39] Disappointingly, however, only very few 2D materials, including phosphorene [40] and defective borophene, [41] have so far been able to simultaneously satisfy the abovementioned two criteria while these coupling materials have yet to be fully explored.…”
Section: Introductionmentioning
confidence: 99%
“…[2] Several approaches, including physical confinement, [3] chemical confinement, [4] integrating sulfur into conductive matrix, [5] interlayers, [6] modified separators, [7] and functional binders, [8] have been developed. In light of this, a small dosage of polar materials such as metal oxides, [11,12] sulfides, [13,14] nitrides, [15] and carbides [16] into sulfur cathodes are extensively investigated.Several polar metal oxides based sulfur hosts were investigated and found to be promising due to strong adsorption of polysulfides on polar surfaces. [9] Considering of the weak interaction between routine nonpolar carbon materials and polar polysulfides, heteroatom doping has been adopted to bind polar sulfur based on guest-host interactions.…”
mentioning
confidence: 99%